Left subclavian artery access for TAVI procedure improves results of treatment of symptomatic aortic valve stenosis in the group of difficult patients. Case report - Krasoń, Marcin; Chodór, Piotr; Walas, Ryszard; Przybylski, Roman; Wilczek, Krzysztof; Niklewski, Tomasz; Głowacki, Jan; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
In this case report we present good result of the transcatheter treatment of the 79 years old male patient with severe symptomatic aortic valve stenosis who presented high surgical risk due to commorbidities and age. Patient suffered from COPD, abdominal aortic aneurysm, tachy-brady syndrome and was proposed aortic valve implantation through left subclavian artery. Presence of aberrant right subclavian artery (arteria lusoria) and left sided cardiac stimulator made the procedure even more interesting. Procedure was carried out without any complications and patient was discharged home in 14th postoperative day.